Pengaruh Ukuran Perusahaan Pada Kebijakan Dividen dengan Kapitalisasi Pasar Sebagai Variabel Mediasi dan Nilai Perusahaan Sebagai Variabel Moderasi - I Kadek Bagiana; Putu Ayu Anggya Agustina (Universitas Negeri Padang, 2021)
Indonesia's economic growth is supported by many companies, one of which is the banking sector. A good company must pay attention to various important factors in managing its operations, one of which is a dividend policy to attract investors to invest their funds. This study aims to re-examine and confirm the effect of firm size on dividend policy with market capitalization as a mediating variable and firm value as a moderating variable. The population in this study is state-owned banks in Indonesia in the 2010-2019 period. Determination of the sample using a non-probability method with purposive sampling technique and obtained as many as 4 banks with a total of 40 observations. The analysis technique used is path analysis. Analysis of the data in this study using SmartPLS 3 software. The results of this study indicate that firm size has a positive effect on market capitalization, firm size has a positive effect on dividend policy, market capitalization has a positive effect on dividend policy, market capitalization mediates the effect of firm size on dividend policy and value firms moderate the effect of market capitalization on dividend policy. Companies in the banking sector are advised not only to pay attention to internal factors that can influence dividend policy but also to the movement of macroeconomic factors. The researcher suggests examining other internal and external factors that are thought to influence dividend policy and market capitalization for further research.